A MODIFIED CPC SOLAR CONCENTRATOR INTENDED TO ACHIEVE WIDER ANGLE OF ACCEPTANCE - TIRUNEH A.T.; DEBESSAI T.; NKAMBULE S.; BWEMBYA G. (Journal of Sustainable Energy, 2020)
The performance of compound parabolic solar concentrators (CPC) is extended through the provision of additional external reflectors that increased the angle of acceptance and hence achieve concentration for longer part of the day. The modified setup increased the angle of acceptance by over 70% while achieving comparatively close concentration ratio ranging between 90-100% of the maximum attainable. For construction of geometry of the reflector profile, an approach involving coordinate transformation has been used. Satisfactory performance of the solar concentrator has been observed for applications involving grey water treatment, production of struvite and drying of fecal matter from urine diversion dry toilets and compost.